Syphilis infection among female sex workers in Nagaland, Northeast India: Analysing their vulnerability to the infection. (March 2013) - Medhi, G K; Mahanta, J; Hazarika, I; Armstrong, G; Adhikary, R; Mainkar, M; Paranjape, R S
This paper describes the sex work characteristics and factors associated with syphilis among female sex workers (FSWs) in Dimapur district of high HIV prevalence Indian state, Nagaland. The study recruited 426 FSWs in 2006 using respondent-driven sampling. The prevalence of syphilis was 21.1% and HIV prevalence was 11.7%. Approximately half were under 25 years of age. Clients were solicited mainly in public places (32.7%), while hotels/lodges/rented rooms were the most common places of entertainment (57.2%). Condom use during the last sex was 36.5% with occasional and 27% with regular clients. Being married, being widowed/divorced/separated, being illiterate or having a history of drug use increased the likelihood of syphilis infection. Entertaining clients in bars/booze joints decreased the probability of syphilis. FSWs who moved between soliciting in public places or bars/booze joints and then entertaining in hotels/lodges/rented rooms had a higher vulnerability to syphilis. In summary, we found that the vulnerability to syphilis among mostly young FSWs in Dimapur varied according to their sex work characteristics, marital and educational status and drug use habits. They may be more vulnerable to HIV and sexually transmitted infections (HIV/STIs) due to the low rate of condom use. The findings have direct implications for HIV/STI prevention programmes in Northeast India.